Filosofia e storiografia nel dibattito anglo-americano sulla svolta linguistica - Bondì, Davide (Premio Tesi di Dottorato, 2013)
This book proposes a critical examination of the main approaches of contemporary historiography, with the aim of bringing out their latent conceptual structures. Reinhart Koselleck wrote that «Historical knowledge always focuses on something more than what is found in the sources»: it is all about making its theories and values explicit, as they are also particular and historical facts themselves, which have clumsily been raised to universal principles. The author brings to light the pre-eminent forms of our relationship with the past through an analysis going from historiography to philosophy - from Pierre Nora, Carlo Ginzburg, Lynn Hunt to Hayden White, Jacques Derrida, Frank Ankersmit; from the New Cultural History and the histoire de la mémoire to the narrativism and to the philosophies of the historical sublime. Going beyond speculation, it is perhaps possible to aspire to a new alliance between historical and philosophical thought, to delimit a "middle space" between the unstructured praxism of a historiography without philosophy to the excessive idealism of a philosophy without history.